An Implementation of Hardware-Accelerated Serial Interface of IoT Gateway for Enabling Machine-Type Communication: A Case Study of Networking IR Controllable Home Appliances - Tsai, Wen-Chung; Zhu, Shi-Xiang; Huang, Nien-Ting; Chiang, Mao-Lun (Journal of Computer Networks and Communications, 2019)
In this paper, we propose an implementation of machine-type communications by combining a novel hardware-accelerated serial interface and a conventional Internet of things (IoT) gateway. Even all home appliances with an infrared (IR) remote controller can be operated through the Internet. In the future, application paradigms will transfer from human-type communications to machine-type communications to provide services such as health care and smart-home control systems. Therefore, commercial IoT gateways are required for intranet-Internet bridging of various wireless access services. Home appliances that are currently used or will foreseeably be used in the future lack network capabilities but can be controlled by an IR remote controller. Accordingly, to leverage existing IR control capabilities, we implemented a smart-home control system, which enables an IR signal to be remotely controlled to emit through the Internet. The implemented system provides a hardware-accelerated serial interface to sample IR signals—including extremely high-frequency signals—and includes a hardware-based data compression mechanism able to reduce the size of oversampled data and save flash memory space. A more intelligent control style can thus be realized by leveraging existing home appliances for the smart-homes of the future.